Detection of biomarkers for inflammatory diseases by an electrochemical immunoassay: the case of neopterin - Centi, Sonia; Tombelli, Sara; Puntoni, Mariarita; Domenici, Claudio; Franek, Milan; Palchetti, Ilaria (Talanta, 2015)
An electrochemical immunoassay for neopterin was developed using recently produced specific antibodies immobilized to protein A-coated magnetic beads in combination with differential pulse voltammetry and screen-printed array of electrodes. Neopterin-alkaline phosphatase conjugate was used as label in a competitive assay format. Multiplexed analysis of neopterin was demonstrated by replacing the traditional ELISA with electrochemical detection and the traditional plastic wells with screen-printed array of electrodes. The optimized electrochemical method, based on polyclonal antibodies, reached a limit of detection of 0.008 ng/mL with an average RSD %=10. Serum samples collected from patients with sepsis, healthy volunteers and other patients without a confirmed clinical diagnosis were also analyzed. The obtained results, compared with those of a commercial ELISA kit, had a significant correlation, showing the possibility to distinguish among the serum samples from ill or healthy subjects.
Keywords: Electrochemical Techniques; Immunoassay; Magnetic beads; Serum samples; zánět; Immobilized Proteins; Neopterin; biologické markery; Biomarkers; sepse; Sepsis; lidé; Electrochemical immunoassay; Antibodies; Biosensing Techniques; Inflammation; Electrodes; imunoanalýza; elektrochemické techniky; biosenzitivní techniky; Screen-printed arrays; elektrody; imobilizované proteiny; protilátky; neopterin; Humans